Unveiling the identity of three Parapsilorhynchus species from the Eastern Ghats: an integrative taxonomic approach - Patel, Rajat Kumar; Thathachari, T K S; Sura, Sameer; Acharya, Smrutirekha; Mohapatra, Sandeep Kumar; Samanta, Luna; Seth, Jaya Kishor; Mishra, Subhrendu Sekhar; Mohapatra, Anil (Journal of Fisheries, 2026)
The identities of Parapsilorhynchus odishaensis, Mahanadhi minnow P. swaini, and P. alluriensis have been elucidated through a comprehensive integration of morphological and molecular data, specifically utilizing mitochondrial cytochrome oxidase subunit 1 (COI) sequences. Specimens collected from the type localities of P. swaini and P. odishaensis, closely resembling their initial descriptions, underwent molecular analysis and were compared to the holotype sequence of P. alluriensis. The genetic distances (K2P) observed among these three species ranged from 0.0% to 2.1%. Notably, the K2P distance between P. swaini and P. odishaensis ranged from 0.2% to 0.3%, while between P. odishaensis and P. alluriensis (holotype) is 1%, and between P. swaini and P. alluriensis (holotype), there was a 0.7% difference. The intraspecific variations among the P. alluriensis sequences, uploaded from the nearby area of the type locality are 0.0 to 0.8%. Despite minor variations in morphological traits such as snout tubercles, anal fin black bar, and inter-orbital space, molecular analysis revealed no significant genetic differentiation among these species. These morphological variations are likely a result of habitat influences. Considering the overlapping morphological features supported by ML tree and ASAP analysis, P. odishaensis, P. alluriensis, and P. swaini (described from the Eastern Ghats) are suggested to be synonymous. As P. odishaensis was the first species described, the other two should be regarded as junior synonyms of P. odishaensis.